Prevalence and Impact of Convergence Insufficiency among school going children of North 24 Parganas District in West Bengal - Debolina Kumar,; Shreya Chakraborty,; Sarbojeet Goswami,; Sudha Prasad,; Khushbu Mishra, (The Bioscan, 2026)
Background: Increasing concern of parents for poor academic performance of their child is a rising concern in school going population in North 24 Parganas district of West Bengal. Convergence Insufficiency (CI) being the most common form of Non- strabismic Binocular Vision Disorder (NSBVA) prevailing in this group can be attributed for the above concern. Aim: To estimate the prevalence of convergence insufficiency in school going children and also its impact on academic performances. Methods: The study included 485 participants: 215 males and 270 females in an age group ranging 6-15 years. Data was collected from school screening camps after detailed history taking and ophthalmic examination. Associated academic performance and involvement in extracurricular activities were also recorded. The diagnosis of CI was based on three criteria – exophoria for near, receded NPC and poor Positive Fusional Vergence (PFV) range. Descriptive analysis was applied on the collected data using statistical software. Results: The average values were calculated as per the age groups. The prevalence of CI in the population pool was 4.90%. Prevalence was more in females about 56% when compared to male 44%. Average break point of NPC was recorded to be 5.42 cm, and average recovery of NPC was 7.44 cm. Average PFV break noted was 27Δ and PFV recovery noted was 13Δ. Conclusion: The struggle to grasp complex subjects can thus be attributed to this cause and need for motivating children for extracurricular activities including physical fitness. This study concludes that in this electronic era, NSBV workup among this group should be emphasized.